Synopsis of the genus Sangaris Dalman in South America (Coleoptera, Cerambycidae), with description of two new species and new combinations - Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2009)
A synopsis of the South American species of Sangaris Dalman, 1823 is presented. Sangaris luteonotata Monné & Monné sp. nov. and S. ordinale Monné & Monné sp. nov. are described from Ecuador. Sangaris luctuosa (Pascoe, 1859) comb. nov. and Sangaris obtusicarinata (Zajciw, 1962) comb. nov. are transferred from Colobothea Lepeletier & Audinet-Serville, 1825. New distributional data are given for S. trifasciata Melzer, 1928, S. zikani Melzer, 1931, and S. luctuosa (Pascoe, 1859). A key to the South American species is provided.